2012
DOI: 10.1074/jbc.m112.355172
|View full text |Cite
|
Sign up to set email alerts
|

Cystathionine Protects against Endoplasmic Reticulum Stress-induced Lipid Accumulation, Tissue Injury, and Apoptotic Cell Death

Abstract: Background:No known function for the amino acid cystathionine other than as an intermediate in cysteine synthesis. Results: Cystathionine prevents ER stress induced steatotic liver injury, acute tubular necrosis and apoptosis without changing induction of the unfolded protein response. Conclusion: Abolition of cystathionine synthesis may contribute to pathogenesis in homocystinuria. Significance: Cystathionine has therapeutic potential for disease states where ER stress is implicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 44 publications
3
52
1
Order By: Relevance
“…Recent studies have suggested the imbalance between the folding of proteins and ER capacity as a cause of apoptosis (18,22), as an excessively prolonged UPR leads cell apoptosis (3,16). Stimulation by albumin overload may cause an accumulation of misfolded proteins in tubular cells and induce sustained ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested the imbalance between the folding of proteins and ER capacity as a cause of apoptosis (18,22), as an excessively prolonged UPR leads cell apoptosis (3,16). Stimulation by albumin overload may cause an accumulation of misfolded proteins in tubular cells and induce sustained ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the classic UPR gene Xbp1, we also found associations in genes with likely roles in ER stress (Dataset S5). CG7140 (human ortholog, H6PD) (28), Calx (NCX) (29), Mgstl (MGST1) (30), Cbs (CBS) (31), and KrT95D (PACS2) (32) are all genes that, when disrupted (in human disease or a model organism), induce or affect the ER stress response. For example, in the mouse, null mutations of H6PD, a gene encoding an ER resident protein, result in up-regulation of UPR associated genes in skeletal muscle (33).…”
Section: Snp In Xbp1mentioning
confidence: 99%
“…Condensation of Hcy and serine can form cystathionine in a reaction catalyzed by cystathionine beta-synthase (MacLean et al, 2012), which is another major mechanism in the Hcy metabolic pathway. Hcy contains a free sulfhydryl group, and oxidizes with other thiols to form mixed disulfides, which results in the oxidization of other substances, including low-density lipoprotein (LDL).…”
Section: Introductionmentioning
confidence: 99%